2022
DOI: 10.1149/ma2022-02142475mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

(Digital Presentation) The Effect of Tartaric-Sulfuric Acid (TSA) Anodizing on the Corrosion Resistance of the AA7475-T761

Abstract: The microstructure of the high strength aluminum alloy, AA7475–T761, in the as-received condition was characterized by optical microscopy, scanning electron microscopy and transmission electron microscopy, and statistical analyses of grain size and micrometer precipitates distribution and density were performed. An anodic aluminum oxide (AAO) film was potentiostatically grown on the alloy in tartaric sulfuric acid (TSA). The anodizing behavior of the alloy and the mechanisms of localized corrosion initiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Copper enrichment/redeposition close to the anodic sites has been reported. [ 41,42,58 ] Similar results were also reported by Moutarlier et al [ 17 ] when studying the corrosion behavior of alloy AA2024‐T3 anodized in sulfuric acid (H 2 SO 4 ).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Copper enrichment/redeposition close to the anodic sites has been reported. [ 41,42,58 ] Similar results were also reported by Moutarlier et al [ 17 ] when studying the corrosion behavior of alloy AA2024‐T3 anodized in sulfuric acid (H 2 SO 4 ).…”
Section: Resultssupporting
confidence: 81%
“…In addition, changes in the morphology of the film have been reported. [ 41,42 ] In recent work from our group, [ 58 ] it was observed that the average depth of the cavities formed was 2.6 ± 1.3 μm for the same alloy anodized under similar anodizing conditions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation